2020
DOI: 10.1002/hbm.25200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen, brain structure, and cognition in postmenopausalwomen

Abstract: Declining estrogen levels before, during, and after menopause can affect memory and risk for Alzheimer's disease. Undesirable side effects of hormone variations emphasize a role for hormone therapy (HT) where possible benefits include a delay in the onset of dementia-yet findings are inconsistent. Effects of HT may be mediated by estrogen receptors found throughout the brain. Effects may also depend on lifestyle factors, timing of use, and genetic risk. We studied the impact of self-reported HT use on brain vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…Townsend deprivation index, and lifestyle score [44][45][46] (see supplementary Note 2 for details on Townsend deprivation index and lifestyle score). In addition, the analyses for reproductive span and age at menopause were corrected for use of HT, use of HC, history of bilateral oophorectomy and/or hysterectomy, and number of live births.…”
Section: Discussionmentioning
confidence: 99%
“…Townsend deprivation index, and lifestyle score [44][45][46] (see supplementary Note 2 for details on Townsend deprivation index and lifestyle score). In addition, the analyses for reproductive span and age at menopause were corrected for use of HT, use of HC, history of bilateral oophorectomy and/or hysterectomy, and number of live births.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, neuroimaging work by Pintzka and Håberg (2015) showed that females who initiated HRT prior to menopause and remained on HRT for at least 3 years (n = 80) had greater whole hippocampal volume compared to HRT-naive females (n = 80) who were matched for ICV and age (ages 51-66). A recent voxelwise study by Boyle et al (2020) also revealed larger gray and white matter volume in various regions in females with a history of HRT (N = 562, ages 71-94) after adjusting for data acquisition site, age, ethnicity, years of education, clinical diagnosis, history of heart disease, Type 2 diabetes, and hypertension, presence of white matter lesions, BMI, physical activity, and past-year estrogen use, but the duration of HRT was not associated with imaging variables.…”
Section: Exogenous Sources Of Estrogen and Progesteronementioning
confidence: 99%
“…In fact, estrogen and progesterone have various molecular and binding mechanisms that modulate neurotransmitter activity, sometimes in opposing directions (Del Río et al, 2018). This variability and lack of consensus of HRT effects on brain structure is a major gap in the literature that requires immediate attention given the growing population of older adults and the high percentage of females taking HRT worldwide (Boyle et al, 2020).…”
Section: Exogenous Sources Of Estrogen and Progesteronementioning
confidence: 99%
“…All participants and their guardians signed written informed consent forms after receiving a complete explanation of the study. To avoid menstrual cycle and age effects on prolactin ( 29 ), we recruited only adult male patients between 20 and 40 years of age.…”
Section: Methodsmentioning
confidence: 99%